If the dinosaurs came back - Most, Bernard (San Diego : Harcourt, 1978)
A young boy who wishes for the return of dinosaurs imagines how useful they would be.
Book Links (A.L.A.)
Horn Book
2.0
K-3.
K-3
Keywords: Dinosaurs -- Fiction; Dinosaurs -- Fiction